Cordycepin induces apoptosis and autophagy in human neuroblastoma SK-N-SH and BE(2)-M17 cells - LI, YIFAN (Oncol Lett, 2015)
Cordycepin, also termed 3′-deoxyadenosine, is a derivative of the nucleoside adenosine that represents a potential novel class of anticancer drugs targeting the 3′ untranslated region of RNAs. Cordycepin has been reported to induce apoptosis in certain cancer cell lines, but the effects of cordycepin on human neuroblastoma cells have not been studied. In the present study, an MTT assay revealed that cordycepin inhibits the viability of neuroblastoma SK-N-SH and BE(2)-M17 cells in a dose-dependent manner. In addition, cordycepin increases the early-apoptotic cell population of SK-N-SH cells, as determined by fluorescence-activated cell sorting analysis. The induction of apoptosis in neuroblastoma cells by cordycepin was further confirmed by western blotting, which revealed cleavage of caspase-3 and poly(adenosine diphosphate-ribose) polymerase 1 in the SK-N-SH and BE(2)-M17 cells. Cordycepin also induced the formation of a punctate pattern of light-chain 3 (LC3)-associated green fluorescence in the SK-N-SH cells transfected with a pEGFP-LC3 vector. Furthermore, western blotting revealed cleavage of LC3 A/B in cordycepin-treated neuroblastoma SK-N-SH cells. Taken together, the results indicate that cordycepin significantly increases apoptosis and autophagy in neuroblastoma cells, and may therefore be a drug candidate for neuroblastoma therapy, but requires additional evaluation.